The morphogenesis-related NDR kinase pathway of Colletotrichum orbiculare is required for translating plant surface signals into infection-related morphogenesis and pathogenesis. - Sayo Kodama; Junya Ishizuka; Ito Miyashita; Takaaki Ishii; Takumi Nishiuchi; Hideto Miyoshi; Yasuyuki Kubo (PLoS Pathogens)
Plant infection by pathogenic fungi involves the differentiation of appressoria, specialized infection structures, initiated by fungal sensing and responding to plant surface signals. How plant fungal pathogens control infection-related morphogenesis in response to plant-derived signals has been unclear. Here we showed that the morphogenesis-related NDR kinase pathway (MOR) of the cucumber anthracnose fungus Colletotrichum orbiculare is crucial for appressorium development following perception of plant-derived signals. By screening of random insertional mutants, we identified that the MOR element CoPag1 (Perish-in-the-absence-of-GYP1) is a key component of the plant-derived signaling pathway involved in appressorium morphogenesis. Constitutive activation of the NDR kinase CoCbk1 (Cell-wall-biosynthesis-kinase-1) complemented copag1 defects. Furthermore, copag1 deletion impaired CoCbk1 phosphorylation, suggesting that CoPag1 functions via CoCbk1 activation. Searching for the plant signals that contribute to appressorium induction via MOR, we found that the cutin monomer n-octadecanal, degraded from the host cuticle by conidial esterases, functions as a signal molecule for appressorium development. Genome-wide transcriptional profiling during appressorium development revealed that MOR is responsible for the expression of a subset of the plant-signal-induced genes with potential roles in pathogenicity. Thus, MOR of C. orbiculare has crucial roles in regulating appressorium development and pathogenesis by communicating with plant-derived signals.